Friction Performance Analysis of Waste Tire Rubber Powder Reinforced Polypropylene Using Pin-On-Disk Tribometer - Sivarao, Subramonian; Qumrul, Ahsan; Mohd , amran; Joseph Sahaya Anand, T; Raja Izamshah , Raja Abdullah (2013)

(untitled)
Waste tire rubber powder reinforced polypropylene composites were established with different set of compositions ranging from 0% to 40%, where coefficient of friction for each of them was analyzed by pin on disk tribometer. The tribological effect between the pin-disk reveals of how the reinforcement plays a vital role in enhancing the coefficient of friction as compared to virgin polypropylene. This paper also elaborates in detail of how the matrix, reinforcement, specimen and test were prepared and conducted via critically designed methodology. A specially designed non-metallic parted line mold was used to ease specimen removal. SEM micrographs provides clearer view of what actually happens between the inter layer bonding of matrix and reinforced materials. The promising findings not only save the environment by utilizing waste tires which are often difficult to be disposed, but it also significantly enhanced the coefficient of friction for pure polypropylene which is highly potential to be used in engineering applications. The correlation between these materials was found towards routing an alternative way of how waste tires could be utilized to engineer new composite materials.